Dry‐Released Nanotubes and Nanoengines by Particle‐Assisted Rolling. (24th May 2013) - Li, Jinxing; Zhang, Jing; Gao, Wei; Huang, Gaoshan; Di, Zengfeng; Liu, Ran; Wang, Joseph; Mei, Yongfeng
<x xml:space="preserve">Abstract</x> Surface tension of self‐assembled metal nanodroplets can be applied to overcome the deformation barriers of strain‐engineered nanomembranes and produce extremely nanoscale tubes. Aggregated nanoparticles stress nanomembranes and subsequently integrate on the walls of rolled‐up nanotubes, which can speed up the tubular engines owing to the enhanced electrocatalytic activity. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>